A Hypothesis: The Interplay of Exercise and Physiological Heterogeneity as Drivers of Human Ageing - Lazarus, Norman R.; Harridge, Stephen D. R. (Frontiers in Physiology, 2021)
As the inherent ageing process affects every facet of biology, physiology could be considered the study of the healthy human ageing process. Where biological health is affected by lifestyle, the continual and continuing interaction of this process with physical activity and other lifestyle choices determines whether the ageing trajectory is towards health or disease. The presentation of both these states is further modified in individuals by the interaction of inherent physiological heterogeneity and the heterogeneity associated with responses and adaptions to exercise. The range of heterogeneity in healthy physiology is circumscribed by the necessity to conform to that of the human species. Our hypothesis is that when sufficient exercise is present, these multiple interactions appear to produce an ageing profile that, whilst functional ability is in decline, remains synchronous, coherent and integrated throughout most of life. In the absence of sufficient physical activity, physiology over time is gradually deteriorating towards the production of a lifestyle disease. Here, the ageing process, interacting with individual physiological heterogeneity, probably determines the age of presentation of a disease as well as the order of presentation of subsequent diseases. In this article we discuss this hypothesis and related concepts in the context of the likely trajectory of healthy, or otherwise, human ageing.